Around the legal definition of a shrine - ADAMCZYK, JERZY (Prawo Kanoniczne, 2014)
This article presents a holistic legal definition of a shrine, which is included in Can. 1230. First, the shrine as a church or other sacred place has been discussed. Next, the other part of the definition of the shrine as a target of numerous pilgrimages of believers has been presented. Another condition for the existence of the shrine is a special reason of piety. Finally, the constitution for establishing the shrine is, in the canonical sense, its approval by the competent ecclesiastical authority.